Case studies of operation management practices in family-run companies - Maia, Tatiane Silva Tavares (Revista Gestão da Produção Operações e Sistemas, 2008)
This study reveals the relationships between organizational culture and production and operations managementpractices in three family-run companies in southern Minas Gerais. The origins, history and contextualaspects highlight the life of these organizations, opening the perspective for considering cultural aspects presentin decisions and actions, taking into account that organizational values are present in these management practices.The study of family-run company values was performed using qualitative research. It was characterizedas a multi-case study using in-depth interviews with directors, founders and successors. It was ascertained thatthe companies studied are highlighted by organizational values that are expressed in planning, organization,direction and control management practices in relation to production and operation activities. The empiricalevidence of the insertion of values in management practices demonstrates that in company operations, the directorsseek to get around the impositions and determinations of administrative rationalization. The systemicnature of a set of values present in service operation and production management practices throughout thehistory of the studied companies reveals a family touch in relationships with clients, employees, family membersand in negotiating with vendors.Key words: Family company; Management practices; Production and operations; Values.